ILLUSTRATED BOOK AS A MEDIA OF INFORMATION ABOUT THE MYTH OF KALIMANTAN KUYANG VERSION OF ACHMAD BENBELA - Nugraha, Rifki; Miftahuddin, Ganjar; Kurniawan, Ivan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
We examined the phenomenon of the myth of kuyang originating from Kalimantan. In the past, it may have only been stories from village to village in Kalimantan but now it is adapted through information media in the form of books, one of which is Achmad Benbela’s novel entitled "Kuyang". The novel focuses on a long narrative and few illustrations so that the information is less clearly described. So it needs to be seen using verbal and visual approach methods in conveying information. In the results of this study due to the lack of reading level so that the media illustration book is more in demand by the public. So that the researcher makes an illustrated book adapted from a novel by Achmad Benbela.